Severe Emphysema Treated by Endoscopic Bronchial Volume Reduction with Lung Sealant (AeriSeal). (23rd April 2013) - Falkenstern-Ge, R. F.; Ingerl, H.; Kohlhäufl, M.
Abstract : Endoscopic lung volume reduction using lung sealant is a very new and innovative treatment option for patients with severe progressive and irreversible lung emphysema. A 55-year-old ex-smoker (60 pack years) referred to our center because of severe lung emphysema with progressive worsening of the obstructive ventilator pattern and clinical condition. We detected collateral channels of this patient by using the Chartis system. Therefore, we decided to treat the advanced emphysema of our patient with endoscopic volume reduction using lung sealant (AeriSeal). The foam of lung sealant AeriSeal is instilled into the peripheral airways and alveoli where it polymerizes and functions as tissue glue on the lung surface in order to seal the target region to cause durable irreversible absorption atelectasis. The follow-up evaluation 12 weeks later showed improved lung function (increased FEV 1/partial oxygen pressure/peripheral oxygen saturation and a reduction of TLC and RV) with improved quality of life. Correlation between changes in primary and secondary outcome measures in the lung function parameters and 6-minute-walking test before and 12 weeks after the application of lung sealant revealed significant reduction of hyperinflation and improvement both in the flow rates and in the physical capability of this patient.